Cyclin B-Cdk1 Kinase Stimulates ORC- and Cdc6-Independent Steps of Semiconservative Plasmid Replication in Yeast Nuclear Extracts - Duncker, Bernard P. (American Society for Microbiology, 1999)
Nuclear extracts from Saccharomyces cerevisiae cells synchronized in S phase support the semiconservative replication of supercoiled plasmids in vitro. We examined the dependence of this reaction on the prereplicative complex that assembles at yeast origins and on S-phase kinases that trigger initiation in vivo. We found that replication in nuclear extracts initiates independently of the origin recognition complex (ORC), Cdc6p, and an autonomously replicating sequence (ARS) consensus. Nonetheless, quantitative density gradient analysis showed that S- and M-phase nuclear extracts consistently promote semiconservative DNA replication more efficiently than G(1)-phase extracts. The observed semiconservative replication is compromised in S-phase nuclear extracts deficient for the Cdk1 kinase (Cdc28p) but not in extracts deficient for the Cdc7p kinase. In a cdc4-1 G(1)-phase extract, which accumulates high levels of the specific Clb-Cdk1 inhibitor p40(SIC1), very low levels of semiconservative DNA replication were detected. Recombinant Clb5-Cdc28 restores replication in a cdc28-4 S-phase extract yet fails to do so in the cdc4-1 G(1)-phase extract. In contrast, the addition of recombinant Xenopus CycB-Cdc2, which is not sensitive to inhibition by p40(SIC1), restores efficient replication to both extracts. Our results suggest that in addition to its well-characterized role in regulating the origin-specific prereplication complex, the Clb-Cdk1 complex modulates the efficiency of the replication machinery itself.